O obesogênico cloreto de tributilestanho provoca anormalidades na função do eixo hipotalâmico-hipofisário-gonadal pela desregulação na sinalização de kisspeptin/leptina em ratas wistar. - Sena, Gabriela Cavati (2017)
Tributyltin chloride (TBT) is a xenobiotic used as a biocide in antifouling paints that has been demonstrated to induce endocrine-disrupting effects, such as obesity and reproductive abnormalities. We investigated whether metabolic disorders as a result of TBT are correlated with abnormal hypothalamus-pituitary-gonadal (HPG) axis function, as well as kisspeptin action. An integrative metabolic control in the HPG axis was exerted by leptin. However, studies that investigate the obesogenic TBT effects on the HPG axis are especially rare. Female Wistar rats were administered vehicle and TBT (100 ng/kg/day) for 15 days via gavage. We analyzed their effects on the tin serum and ovary accumulation (as biomarker of TBT exposure), estrous cyclicity, surge LH levels, GnRH expression, kisspeptin action, fertility, testosterone levels, ovarian apoptosis, uterine inflammation, fibrosis, estrogen negative feedback, body weight gain, insulin, leptin, adiponectin levels, as well as the glucose tolerance (GTT) and insulin sensitivity tests (IST).